2008
DOI: 10.1524/ract.2008.1498
|View full text |Cite
|
Sign up to set email alerts
|

Development of an electrochemistry apparatus for the heaviest elements

Abstract: Electrochemistry / Flow electrolytic cell / Chemically modified electrode / Redox reaction Summary. We developed a new apparatus for the study of electrochemical properties of the heaviest elements. The apparatus is based on a flow electrolytic cell combined with column chromatography. Glassy-carbon fibers modified with Nafion perfluorinated cation-exchange resin are used as a working electrode as well as a cation-exchanger. The elution behavior of 139 Ce with the number of 10 10 atoms in 0.1 M ammonium α-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…These results confirm that Rf is a member of the group-4 elements in the Periodic Table [7][8][9][10]. On the contrary, fluoride complex formation of Rf is significantly different from that of the homologs Zr and Hf, demonstrating a surprising behaviour of Rf [15][16][17][18]. Here, we summarize the fluoride complex formation studies of Rf performed with ARCA II and AIDA.…”
Section: Element 104 Rutherfordium (Rf)supporting
confidence: 62%
See 3 more Smart Citations
“…These results confirm that Rf is a member of the group-4 elements in the Periodic Table [7][8][9][10]. On the contrary, fluoride complex formation of Rf is significantly different from that of the homologs Zr and Hf, demonstrating a surprising behaviour of Rf [15][16][17][18]. Here, we summarize the fluoride complex formation studies of Rf performed with ARCA II and AIDA.…”
Section: Element 104 Rutherfordium (Rf)supporting
confidence: 62%
“…The successive fluoride complex formation of cationic species of Zr, Hf, and Rf was investigated through cation-exchange chromatography with ARCA II at the Philips Cyclotron, Paul Scherrer Institute [15] and with AIDA at the JAEA tandem accelerator [16][17][18]. The results demonstrated that the distribution coefficient, K d , of Rf in mixed solution of HF/0.10 M HNO 3 decreases with increasing concentration of the fluoride ion, [F − ], indicating the consecutive formation of neutral and/or anionic fluoride complexes of Rf as those of homologs.…”
Section: Element 104 Rutherfordium (Rf)mentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, we have developed a novel method of electrolytic column chromatography available for single ions. 15 Carbon fibers modified with a Nafion perfluorinated ionexchange resin were employed as a working electrode as well as a cation exchanger. This technique was successfully applied to the oxidation of nobelium (No).…”
mentioning
confidence: 99%